A late-diagnosed phenylketonuria case presenting with autism spectrum disorder in early childhood - Mazlum, Betül; Anlar, Banu; Kalkanoğlu-Sivri, H. Serap; Karlı-Oğuz, Kader; Özusta, Şeniz; Ünal, Fatih (The Turkish Journal of Pediatrics, 2016)
Phenylketonuria is one of the most prevalent autosomal recessive hereditary disorders in Turkey. If untreated, it results in severe brain damage and can also be associated with autism in certain patients. We present a three-year old boy who exhibited the symptoms of autism and was subsequently diagnosed with phenylketonuria. This case illustrates that because the majority of autism cases are idiopathic, an occasional patient with a metabolic disorder might be overlooked especially in the era of newborn screening. We also discuss the possible pathogenetic processes leading to autistic symptoms in phenylketonuria, and wish to draw attention to the possibility of cases missed in the screening program because of less than 100% coverage or insufficient food intake before blood sampling. Clinicians should keep in mind the possibility of treatable disorders in children with autism even when such disorders appear unlikely.
Keywords: autism; excitotoxicity; glutamate; phenylketonuria